Corrosion Protection of Aluminum Alloy by Sol-Gel Derived Organic-Inorganic Hybrid Pretreatments Based on Epoxy Resin Modified Silane Precursor - Mahshid Niknahad, Mahshid Niknahad; J. Patel, Chintankumar; Mannari, Vijay (Journal of Coating Science and Technology, 2016)
Organic-Inorganic hybrid (OIH) derived by sol-gel process have emerged as promising pretreatments alternative to conventional chromate-based systems for aluminum alloys. In this study novel organo-silane precursor has been synthesized from epoxy resin and amino-silane compound and used as the primary component of OIH film. The effects of epoxy and silane functionality and organic inhibitor used in the composition have been studied on corrosion resistance performance of aluminum alloy (3003-H14). The study also investigates the performance of top coat (powder coating) adhesion onto the pretreatment under different cure conditions. The chemical structure of sol-gel precursor (epoxy silane) and the deposited films have been characterized by FTIR analysis. The corrosion protection performance has been studied by electrochemical impedance spectroscopy (EIS), D.C. electrochemical polarization measurements, and the accelerated neutral salt spray test (ASTM B117). This study shows that by proper choice of precursor structure, functionality, processing conditions, and corrosion inhibitor amount, it is possible to derive OIH films with corrosion resistance performance comparable to conventional Cr (VI) based pretreatments.